Answer:
• (a)-i
,
• (b)17+11i
Explanation:
Part A
We are to express the complex number i²³ in the simplest form.
![\begin{gathered} First\text{ write the index as a sum of an even and an odd number} \\ i^{\mleft\{23\mright\}}=i^(22+1) \\ \text{Next, separate using the addition law of indices} \\ =i^(22)* i^1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/bom8kxnaizizppzxit92o4vsxw08c30h1j.png)
Then rewrite in the form below:
![\begin{gathered} =(i^2)^(11)* i^{} \\ U\sin g\text{ the fact that: }i^2=-1 \\ (i^2)^(11)* i^{}=(-1)^(11)* i=-1* i=-i \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/n54pkx6h96j9hu94sw5s6qyhp0f8vntlw8.png)
Therefore:
![i^(23)=-i](https://img.qammunity.org/2023/formulas/mathematics/college/h7o81k3qq5ne3y8vscdt95jw49nmzrn7fc.png)
Part B
Given the complex expression:
![4\mleft(3+4i\mright)-5i\mleft(1+i\mright)](https://img.qammunity.org/2023/formulas/mathematics/college/lvu0xp4v2jicg41r02jp56kdybrnzzdomm.png)
First, open the brackets:
![\begin{gathered} =12+16i-5i-5i^2 \\ =12+11i-5i^2 \\ i^2=-1 \\ \implies=12+11i-5i^2=12+11i-5(-1) \\ =12+11i+5 \\ =12+5+11i \\ =17+11i \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/st3po19l44bstj38zf5r8x5yeowne6lyjs.png)
The complex number in standard form is 17+11i.